A-statistical approximation of generalized Szasz-Mirakjan-Beta operators - Ozarslan, Mehmet Ali; Aktuglu, Huseyin (Pergamon-Elsevier Science Ltd, 2011)
In this paper we prove a Korovkin type approximation theorem and obtain the rate of convergence of the generalized Szasz-Mirakjan-Beta operators by means of modulus of continuity and elements of Lipschitz class. Furthermore we give the A-statistical approximation theorem for these operators and investigate the case which provides the best estimation. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Positive linear operators; Korovkin type theorems; Summation-integral type operators; A-statistical convergence and statistical convergence; Szasz-Mirakjan-Beta operators